2021
DOI: 10.1159/000512916
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Inflammatory Markers in Patients with Pemphigus Vulgaris

Abstract: <b><i>Background:</i></b> Emerging evidence indicates that several hematological markers can be used to evaluate treatment response, prediction, and early relapse detection in different inflammatory conditions. This study aimed to investigate the correlation between the neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, platelet-to-neutrophil ratio, mean platelet volume, and disease activity in patients with pemphigus vulgaris. <b><i>Methods:</i></b> F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…The median age of the patients participating in the study was 47 years, which is within the range reported in the literature [16]. A female predominance was observed in this study, as in previous epidemiologic studies of PV [17].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The median age of the patients participating in the study was 47 years, which is within the range reported in the literature [16]. A female predominance was observed in this study, as in previous epidemiologic studies of PV [17].…”
Section: Discussionsupporting
confidence: 85%
“…Two markers of systemic inflammation, the NLR and the PLR, which are correlated with the activity and severity of PV, were found to be elevated in patients with candidiasis, and elevated levels of these markers were, in turn, associated with a high risk of developing candidiasis [ 16 ]. The elevated levels of the NLR presented in this study may be attributed to an activated immune response to PV activity or relapse, as well as to a bacterial infection resulting in increased neutrophils and decreased lymphocytes, the latter being further decreased in inflammatory conditions and with megadoses of corticosteroids [ 16 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lyakhovitsky and colleagues [ 29 ] in a recent paper also confirmed the validity of neutrophil and lymphocyte counts in pemphigus patients. Admittedly, their study was based on assessing the neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, platelet-to-neutrophil ratio and mean platelet volume, without addressing the activation of these cells during the course of the disease.…”
Section: Discussionmentioning
confidence: 75%
“…This was based on their observation of the NLR and PLR correlating positively, and the MPV and PNR correlating negatively with the disease activity, with the NLR showing a more significant correlation in patients not treated with rituximab. [ 37 ] Lin and Li observed NLR and PLR (together with monocyte count and antibodies against Dsg 1 and Dsg 3) correlating positively with the pemphigus vulgaris disease activity with the NLR, low albumin-to-globulin ratio, and high anti-Dsg1 antibody levels being associated with pemphigus area disease index scores. The authors believe these findings could be more comprehensive and objective reflectors of the pemphigus vulgaris disease severity.…”
Section: Introductionmentioning
confidence: 99%